The Analysis of Customer Readiness Towards New Self Service Technologies in Retail - Matić, Matea; Prskalo, Daria (Oeconomica Jadertina, 2017)
The aim of this paper is to explore customer readiness towards new self-service technologies in retail. In addition to that, the aim of this paper is to explore and determine the attitude and intentions of customers in using new self-service technologies and to determine the perceived trust towards new self-service technology trends in retail stores. The data was collected through a survey questionnaire using a sample of 213 respondents of generation Y from the Dubrovnik-Neretva County. Research results indicate that consumers show a high level of readiness toward new self-service technologies and moderate high level of perceived trust toward smart self-service carts in retail stores. Additionally, it indicates that customers show positive attitudes toward new self-service technology trends such assmart self-service carts and most of them intend to use that technology in their future purchases.
Keywords: self-service technology; customer readiness; customer intentions.